Peningkatan Kedisiplinan Datang di Sekolah Melalui Layanan Konseling Behavioral di SMK - Daroji, Daroji (Manajemen Pendidikan, 2016)
The purpose of this study is to determine the effectiveness of behavioral counseling techniques behavior contract to improve discipline arrive on time at school in class XII student of SMK N 1 Surakarta odd semester of 2014/2015 academic year.This research is a measure of guidance and counseling (PTBK). This study is conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. The subjects are  students of class XII SMK Negeri 1 Surakarta totaling three  students. Source of data derived from students. The data collection technique is by observation and interviews. The validity of the data using a triangulation method. Analyzed using percentages and clinical analysis.The results showed that through group counseling to reduce anxiety entering the work of students from pre-cycle to the first cycle and from the first cycle to the second cycle. In the first cycle, the average percentage change of 21.21%. The anxiety of students has decreased, although not significantly. In the second cycle, the average percentage change of54.33%, which means the results of the research has reached an indicator of success. The conclusions of this research is behavioral counseling with the contract effective technique to improve discipline arrive on time in class XII student of SMK Negeri 1Surakarta odd semester of 2014/2015 academic year.